2015
DOI: 10.1080/21640629.2016.1157324
|View full text |Cite
|
Sign up to set email alerts
|

Disability sports coaching: towards a critical understanding

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 66 publications
0
75
0
4
Order By: Relevance
“…To date, the body of literature focused on disability sport coaches is primarily descriptive and "coach-centric" (Townsend, Smith, & Cushion, 2016). The learning experiences of coaches in disability sport have been explored extensively and in isolation from their athletes (e.g., Cregan, Bloom, & Reid, 2007;Duarte & Culver, 2014;McMaster, Culver, & Werthner, 2012), despite the complex interactions and relational processes that shape the experiences of both coach and athlete.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the body of literature focused on disability sport coaches is primarily descriptive and "coach-centric" (Townsend, Smith, & Cushion, 2016). The learning experiences of coaches in disability sport have been explored extensively and in isolation from their athletes (e.g., Cregan, Bloom, & Reid, 2007;Duarte & Culver, 2014;McMaster, Culver, & Werthner, 2012), despite the complex interactions and relational processes that shape the experiences of both coach and athlete.…”
mentioning
confidence: 99%
“…Limited knowledge of and experience with disability may hinder coaches' ability to understand, reflect, and empathize with athletes. Among the few resources available for disability sport coach development, impairment-specific knowledge and skills are often emphasized (i.e., the focus is on coaching to improve sport performance against the limitations of impairment; Townsend et al, 2016). In other words, the medical model of disability -in which impairment is viewed as a personal tragedy and a problem to be solved (Smith & Perrier, 2014;Thomas, 2004) -frequently underpins coach education and discourse in disability sport.…”
mentioning
confidence: 99%
“…All the student‐coaches in this study emphasised that they felt they had improved their able‐bodied coaching practice by working with people with SEN and disabilities. While there is minimal literature devoted to this specific area (DePauw and Gavron, ; Townsend et al ., ), what is known is that sustained, focused, and appropriate practice is critical in the developmental learning pathway that coaches undertake (Lyle, ; Martens, ; North, ; Navin, ). Consistent with almost all previous coach learning literature centred on the basic coaching skills (Coaching Review Panel, ; Jones, ; Cushion et al ., ), the coaches in this study suggested that a focus on adaptability, instinct, and communication within the SEN and disability sessions was extremely important and transferred well to able‐bodied coaching.…”
Section: Resultsmentioning
confidence: 99%
“…While there are still question marks over the extent to which coaches feel they are prepared for coaching people with SEN and disabilities in the UK (Townsend, Smith, and Cushion, ) and abroad (Kozub and Porretta, ; Flores, Beyer, and Vargas, ), it is probably fair to say that we do have a reasonable understanding of how, at a basic level, coaches can work in special educational needs (SEN) and disability sport (Robbins, Houston, and Dummer, ; Tawse, Bloom, Sabiston, and Reid, ; Schliermann, Stolz, and Anneken, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation